Microstructure of TiAl15Si15 Alloy Prepared by Powder Metallurgy - Knaislová, Anna; Novák, Pavel; Průša, Filip; Kopeček, Jaromír (Manufacturing Technology Journal, 2018)
This work deals with the microstructure of TiAl15Si15 intermetallic compound, which can be used as a high-temperature low-weight material especially for the automotive and aerospace industry. A combination of high mechanical properties, good oxidation resistance and low density of this material is a good potential for use this alloy in many applications. The TiAl15Si15 alloy was prepared by different techniques of powder metallurgy. In this work, microstructure after reactive sintering, reactive sintering in a combination of Spark Plasma Sintering and mechanical alloying followed by Spark Plasma Sintering was described. The results were compared with the same alloy prepared by arc melting.
Keywords: Reactive sintering; Mechanical alloying; Spark Plasma Sintering; Arc melting